Students’ Digital Media Usage at the University of Tübingen During the CoViD19 Semester 2020 Compared to 2018 - Taiga Brahm; Marina Pumptow (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung, 2021)
The purpose of this study was to compare students’ digital media use during the so-called corona semester in summer of 2020 when universities worldwide moved to online teaching and learning, with data from 2018. Two research questions were at the center of our study: To what extent did students’ media use during the digital summer semester 2020 differ from media use in 2018? In which ways is media use in 2020 related to individual factors (e.g., emotional states, social integration, self-efficacy)? In 2020, 207 students at the University of Tübingen participated in an online survey on their digital media use. This data was compared with an existing data set from the same university from 2018 (N = 808 students). Results show a significant increase in students’ media use across all categories, in particular Learning Management System, online exercises, learning videos, and video conferencing. We also found a significant relation of students’ usage of online tools for learning with their feeling of social integration, as well as connections between students’ digital media self-efficacy and their learning-relevant emotions. The article discusses these results in the light of other studies on students’ media uses and provides first practical implications for lecturers.